ISLAMIC BUSINESS ETHICS IN LAW ACTIONOLOGY - Rahmat Fadillah (Muamalat: Jurnal Kajian Hukum Ekonomi Syariah, 2019)
Islamic business is currently starting to explore various types of businesses and entering the farthest geographical area. In Islamic business, we guarantee the quality, and quantity of goods, as well as the services offered or those that are intended to be used, for the sake of creating a common hope that is a good pleasure. Not a little in the Islamic business there is no pleasure. One of the causes of the loss of pleasure is due to the lack of attainment of ethics in the Islamic business itself. Sometimes one of the parties implementing the Islamic business transaction does not understand correctly, or cannot present good ethics in conducting Islamic business. This paper is a form of analysis that explains what forms of ethics in legal axiology are used in Islamic Business. Because ethics is a very important thing.